Combined shear/tension testing of fibre composites at high strain rates using an image-based inertial impact test - Fletcher Lloyd; Van-Blitterswyk Jared; Pierron Fabrice (EPJ Web of Conferences, 2018)
Testing fibre composites off-axis has been used extensively to explore shear/tension coupling effects. However, off-axis testing at strain rates above 500 s-1 is challenging with a split Hopkinson bar apparatus. This is primarily due to the effects of inertia, which violate the assumption of stress equilibrium necessary to infer stress and strain from point measurements taken on the bars. Therefore, there is a need to develop new high strain rate test methods that do not rely on the assumptions of split Hopkinson bar analysis. Recently, a new image-based inertial impact test has been used to successfully identify the transverse modulus and tensile strength of a unidirectional composite at strain rates on the order of 2000 -1. The image-based inertial impact test method uses a reflected compressive stress wave to generate tensile stress and failure in an impacted specimen. Thus, the purpose of this study is to modify the image-based inertial impact test method to investigate the high strain rate properties of fibre composites using an off-axis configuration. For an off-axis specimen, a combined shear/tension or shear/compression stress state will be obtained. Throughout the propagation of the stress wave, full-field displacement measurements are taken. Strain and acceleration fields are then derived from the displacement fields. The kinematic fields are then processed with the virtual fields method (VFM) to reconstruct stress averages and identify the in-plane stiffness components G12 and E22.